ICT, the City and Society - Galit Cohen; Peter Nijkamp (Tinbergen Institute, 2002)
Information and Communication Technologies (ICT) have become important tools to promote a variety of public goals and policies. In the past years much attention has been given to the expected social benefits from deploying ICT in different fields (transportation, education, public participation in planning etc.) and to its potential to mitigate various current or emerging urban problems. The growing importance of ICT in daily life, business activities and governance prompts the need to consider ICT more explicitly in urban policies. Alongside the expectation that the private sector will play a major role in the ICT field, the expected benefits from ICT encourage also urban authorities to formulate proper public ICT policies.Against this background, various intriguing research questions arise. What are the urban policy-makers' expectations about ICT? And how do they assess the future implications of ICT for their city? An analysis of these questions will provide us with a better understanding of the extent to which urban authorities are willing to invest in and adopt a dedicated ICT policy.This paper is focusing on the way urban decision-makers perceive the opportunities of ICT policy. First, a conceptual model is developed to explain the driving forces of urban ICT policies in European cities. Next, by highlighting the importance of understanding the decision-maker's black box, we identify three crucial variables within this box. In the remaining of the paper we will give an operational meaning to these three variables by using a survey comprising more than 200 European cities . By using statistical multivariate methods (i.e., factor and cluster analysis), we were able to characterize the decision-makers according to the way they perceive their city (the imaginable city), their opinion about ICT and the way they asses the relevance of ICT policies to their city.
Keywords: R00; R1; R5; 330; ICT policy; public policy-making; urban policies; factor analysis; cluster analysis; Informationstechnik; Forschungs- und Technologiepolitik; Faktorenanalyse; Europa